The spectrum of teaching styles in physical education - SueSee, Brendan; Hewitt, Mitch; Pill, Shane; Routledge (Firm) (New York : Routledge, 2020)
"This is the first in-depth, practice-focused book to explain 'spectrum theory' and its application in physical education and sports coaching. Spectrum theory identifies eleven distinct teaching styles, with decision-making as a central characteristic, and allows teachers to select age and developmentally appropriate styles across social, physical, ethical, emotional and cognitive channels. The book brings together leading thinkers in spectrum theory, to demonstrate how it can be applied to improve teaching and learning in PE and coaching. Drawing on real-world research in schools and universities, the book considers the history of spectrum theory, and examines its significance across important areas such as physical education teacher education, sport pedagogy, teacher development, models such as Games Sense and Teaching Games for Understanding, skill acquisition, and student learning and perception. Every chapter highlights the practical implications of research in real-world settings and considers how spectrum theory can enhance learning experiences. This book is invaluable reading for all pre-service and in-service school physical education teachers, sports coaches, school pedagogical leaders and college lecturers"--
OCLC-licensed vendor bibliographic record.
Keywords: Physical education and training -- Study and teaching; Coaching (Athletics) -- Study and teaching; EDUCATION / Teaching Methods & Materials / General; EDUCATION / Physical Education; SPORTS & RECREATION / General